Transport mechanism of urate in humans - Sakurai, Hiroyuki (Henry Stewart Talks, 2016)
Urate physiology and pathophysiology, Physiology of trans-epithelial movement of the solute, Urate handling in the kidney, Urate handling in the intestine, Drugs and urate